Pengalaman Guru Mendampingi Regulasi Emosi Anak Intellectual Disability dalam Interaksi Sosial di SLB Amanah Padang - Wahyudi, Muhammad; Deya, Citra Rahma; Hapsari, Friskha; Zalmy, Shaztry; Rahayu, Wirza Feny (CV. ITTC INDONESIA, 2025)
Children with intellectual disabilities often experience challenges in social interaction due to limited emotional regulation skills. This study aims to explore the role of emotion regulation in shaping the social interactions of children with intellectual disabilities. Using a descriptive qualitative approach and a case study method, the research focuses on a single student at SLB Amanah Padang. The findings reveal that the subject has difficulty recognizing, managing, and expressing emotions appropriately. Emotional regulation difficulties are closely linked to impulsive behavior, limited peer relationships, and emotional withdrawal. The unsupportive family environment further hinders emotional development, as the subject’s parents also have intellectual disabilities. Nevertheless, teacher support plays a crucial role in developing the child’s emotional and social skills through individualized approaches and positive reinforcement. This study underscores the importance of emotional intervention strategies in special education settings to improve both emotional regulation and social competence in children with intellectual disabilities.